Analisis Perbedaan Liquiditas Saham, Kinerja Keuangan, dan Return Saham di Sekitar Pengumuman Stock Split - Muharam, Harjum; Sakti, Hanung (Journal the Winners: Economics, Business, Management, and Information System Journal, 2008)
Using 13 samples from listed companies in Jakarta Stock Exchange within 2003-2005, this article analyze the difference of stock liquidity, financial performance, and stock return in the period of stock split announcement. Multivariate Analysis of Variance (MANOVA) shows that there is no difference in Trading Volume Activity (TVA) of stock and financial performance before, within, and after stock split announcement, but this study finds that the difference in stock return exist in the period of stock split announcement.